Experimental Study on Parameters Affecting the Runout Range of Rockfall - Jie Hu; Shucai Li; Shaoshuai Shi; Liping Li; Qian Zhang; Hongliang Liu; Peng He (Advances in Civil Engineering)
This paper presents the law of rockfall runout range and the effect on lateral dispersion caused by different parameters. A creative combined model test bench was developed as the test site, the slope, and blocks were artificial using similar materials that can meet the strength required in the experiment. As to the analysis of rockfall runout range, a series of experiments were carried out, and the shape, weight, and release heights of blocks were varied to clarify the effect of 3 factors. The motion trajectory of block was recorded based on a high-speed camera and a defined coordinate system. In addition, the final longitudinal and lateral runout distances of block were also measured. Furthermore, an extended laboratory investigation was conducted, consisting of 160 tests with cubical blocks, and an empirical model was proposed from the test results that estimates the lateral dispersion W/L of cubical blocks with different mass and release height. For the design of practical mitigation measures, the research results in this paper may provide a useful reference.